THE DEVELOPMENT OF AGROTOURISM IN AZERBAIJAN: BASED ON THE ITALIAN EXPERIENCE - Mirali Hasanzadeh (Agora International Journal of Economical Sciences (AIJES), 2023)
Agrotourism, an innovative type of rural tourism, is growing quickly across the world. Agrotourism is seen as a vital factor in increasing farmer prosperity, boosting economic growth, and improving the general quality of life in remote areas by visitors' incoming. Promoting this type of tourism in Western European nations has been a main goal as attaining long-term growth and started developing during the 1960s. Azerbaijan's principal priority is the sustainable development of diverse economic sectors, and increasing agrotourism stands out as a vital goal within this context. This article investigates Italian viewpoints regarding agrotourism and strategies to implement and promote its growth, as well as, submit proposals for the expansion of agrotourism and policy implementation in Azerbaijan. The study encompassed in-depth information on the Azerbaijani tourism industry, including programs implemented through cooperation between governmental and non-governmental organizations to promote advancement of agrotourism. The exploration bases its findings on recent investigations, information from statistics, and research papers.
Keywords: 330